2019
DOI: 10.1142/s2424786319500208
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral biases and investors’ decision-making: The moderating role of socio-demographic variables

Abstract: The purpose of this study is to investigate the impact of behavioral biases on investment decision, and the interaction effect of socio-demographic characteristics. Data were collected from a sample of 179 individual investors in the Pakistan Stock Exchange (PSX). The authors conducted a hierarchical regression analysis to test the moderating effect of socio-demographic variables on behavioral biases. The results show that behavioral biases have a significant impact on investors’ decision-making. Moreover, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…This is because, investors assume that the trustworthiness and helpfulness of information generated through herding is extremely high. Further, Katper et. al.…”
Section: Herd Mentality Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…This is because, investors assume that the trustworthiness and helpfulness of information generated through herding is extremely high. Further, Katper et. al.…”
Section: Herd Mentality Biasmentioning
confidence: 99%
“…Among different studies on investigating the effect of socio-demographic factors, Katper et al (2019) investigated the interaction effect of occupation on investors' decision-making in the Pakistan Stock Exchange. They finally identified that representativeness bias interacting with occupation shows an inverse effect on investors' decision.…”
Section: Occupationmentioning
confidence: 99%
See 3 more Smart Citations